2020
DOI: 10.1021/acs.est.0c01306
|View full text |Cite
|
Sign up to set email alerts
|

Permeability is the Critical Factor Governing the Life Cycle Environmental Performance of Drinking Water Treatment Using Living Filtration Membranes

Abstract: Living Filtration Membranes (LFMs) are a water filtration technology that was recently developed in the lab (Technology Readiness Level 4). LFMs have shown filtration performance comparable with that of ultrafiltration, far better fouling resistance than conventional polymer membranes, and good healing capabilities. These properties give LFMs promise to address two significant issues in conventional membrane filtrationfouling and membrane damage. To integrate environmental considerations into future technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Issue) : 2023 purity of the SCOBY can be used as a filtering material. The previous studies show that the 90% rejection of the 30nm particle, 98% rejection of 50nm particle, and 99% rejection of 100 nm particles was seen (Jiang et al, 2020). This shows it can remove most of the contaminants and some bacteria and protozoa.…”
Section: Resultsmentioning
confidence: 82%
“…Issue) : 2023 purity of the SCOBY can be used as a filtering material. The previous studies show that the 90% rejection of the 30nm particle, 98% rejection of 50nm particle, and 99% rejection of 100 nm particles was seen (Jiang et al, 2020). This shows it can remove most of the contaminants and some bacteria and protozoa.…”
Section: Resultsmentioning
confidence: 82%
“…This study indicated that LFMs also experience an increased resistance to biofouling compared to a commercial MCE membrane. A publication using preliminary LFM and MCE data suggested that this resistance to fouling may reduce the life cycle environmental impacts of ultrafiltration considerably compared to commercial polymer membranes . In addition to filtration membranes, bacterial cellulose (BC) is also being investigated as a wound dressing, where BC grown from Acetobacter specifically may be useful for mitigating biofilms and infections within the field of medicine.…”
Section: Resultsmentioning
confidence: 99%
“…The LFM flux outperformed that of the commercial membranes by 19, 33, and 40%, as measured by the percent difference in flux decline after filtering 250 mL of water at constant pressure. LFM's resistances to fouling could considerably reduce the life cycle environmental impact of ultrafiltration compared to a conventional polymer membrane, 42 and this may translate to more successful applications of water filtration membranes in the future.…”
Section: ■ Introductionmentioning
confidence: 99%